Health Education for Peon to Improve Infection Prevention Practices in Government Health facilities of Morang - Gurung, Gagan; Dahal, S. (Journal of Nepal Health Research Council, 2009)
Not uploaded.Key words: Decontamination; Hand washing; Infection Prevention; Waste disposal.DOI: 10.3126/jnhrc.v6i1.2444Journal of Nepal Health Research Council Vol. 6, No. 1, Issue 12, April, 2008 Page: 49-52